Ownership and Utilization of Long-Lasting Insecticide Treated Nets in Woji Obio Akpor L.G.A Rivers State - Obisike, Victor Ugochukwu; Dike, Maduabuchi Chizuruoke; Ikem-Chima, Chinwenmeri (British Journal of Healthcare and Medical Research, 2025)
Malaria is a life-threatening disease caused by parasites that are transmitted to people through the bites of infected female Anopheles mosquitoes. It is preventable and curable, however, efforts made to eradicate malaria in Nigeria totally have proved abortive. The study aims at determining the ownership and utilization of long-lasting insecticide treated nets in Woji Obio Akpo L.G.A in Rivers State. The study adopted a cross-sectional descriptive research design. Data for this study was collected from the respondents through the use of questionnaires. Questionnaires were shared to all 360 respondents which were randomly selected using Bourley Proportion Allocation formula, which determined number of respondents per household in each village, and field surveys through responses to questions in the questionnaire served as the main source of primary data for this study. From the tables, 276 of 76.7% have idea about treated nets. Moreso, only 174 of 48.3% have nets and out of that number, only 154 (94.4%) use nets. In conclusion, Ownership and utilization of long-lasting insecticide-treated nets (LLINs) play a crucial role in preventing malaria and reducing the burden of the disease. The widespread distribution of LLINs has been successful in increasing their ownership and availability, particularly in malaria-endemic regions. However, the challenge lies in ensuring optimal utilization and consistent use over time.